Simulation Study of the Secondary Arc Extinction due to Single Line to Ground Fault on the Thailand 500 kV Line from Mae Moh to Tha Ta Ko - K. Ngamsanroaj (2018)
Successful operation of a power system depends largely on the ability to provide reliable and uninterrupted service to the loads. Single phase switching has become an increasingly more viable approach to the operation of EHV systems in recent years. Indeed, single phase reclosing, if successful, represents a significant step in improving system performance and is an attractive, economical means of obtaining acceptable transient stability with fewer lines. Single phase reclosing has the additional benefits of reducing switching overvoltages. This paper describes the simulation study of secondary arc extinction due to single line to ground fault and then clearing the faulted line. The work is performed by EMTP on the Thailand 500 kV transmission line from Mae Moh to Tha Ta Ko. Various responses of simulation results are presented.